If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 100a + 150b = 0 Solving 100a + 150b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-150b' to each side of the equation. 100a + 150b + -150b = 0 + -150b Combine like terms: 150b + -150b = 0 100a + 0 = 0 + -150b 100a = 0 + -150b Remove the zero: 100a = -150b Divide each side by '100'. a = -1.5b Simplifying a = -1.5b
| (x/4)-6=22 | | 4[t+5]-3=6t-13 | | (z)5-1=0 | | -67=6x-12+5x | | 4-6x=-4x-18 | | 3m+4n+6n= | | (1/3)h-4((2/3)h-3 | | m^3p^2q^10/m^-2p^4q^-6= | | 4-5x=3x+1 | | 40=1.69n | | -12-(-30)= | | 35-2x=x^2 | | 44x+2=45 | | 44/5÷11/4 | | 6x+9=27-2x | | 1/5=×/15 | | a=x^2-30x+225 | | A+-70=2 | | 4-5lnx=8 | | 12x^2-75x+85.25=0 | | Y=1x+13 | | 24x^2+36x^3= | | 7=4g-5 | | a=22 | | 3/8=y/5 | | 6-5x+6x=18 | | 6-5x+6=18 | | 2x^4-6x^3-128=0 | | 26=-4+5n | | y=10-6y | | 3a+5=-2a+24 | | 2x^4-6x^3=128 |